Vietnam Veterans : War Atrocities, Social Connections and Assimilation - Carll, Brad (My University, 2009)
The Vietnam War was unlike any war that America has ever been a part of. The experiences of unconventional warfare affected many coming back to America. Since Vietnam, Historians have looked at Vietnam and asked "what went wrong?" When examining the failures of the Vietnam War, the most apparent problem was the failure to provide support for enlisted men to assimilate back into American culture. In order to examine the problems of assimilation, a random sample of twenty Vietnam veteran oral histories were analyzed. This paper focuses on social connections developed during and after the war, and how they affected assimilation. Many veterans did not have a problems adapting back into American society because of the support networks that the soldiers created or maintained during war.
Keywords: Vietnam War, 1961-1975--Social aspects; Vietnam War, 1961-1975--Veterans--Services for; Vietnam War, 1961-1975--Veterans--Social networks